High-quality preparation method of metal heat-conducting gasket by strengthening process
High-precision processing of metal thermal gaskets through focusing ion beam technology solves the problem of difficult control of surface roughness and thermal contact performance in traditional methods, and achieves efficient and personalized heat dissipation performance, reducing energy consumption and environmental pollution.
Patent Information
- Application Number
- CN202411751873.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Traditional metal thermal gasket preparation methods are difficult to accurately control surface roughness and thermal contact performance, cannot meet the needs of efficient heat dissipation and personalization, and there are problems of high energy consumption and environmental pollution.
Focused ion beam technology is used for high-precision processing, etching selectivity is enhanced through ion implantation pretreatment, surface roughness is accurately controlled, specific thermal contact requirements are met, and differentiated roughness customization is achieved in different regions.
It significantly improves the thermal contact performance and thermal conductivity of metal thermal gaskets, meets complex and fine heat dissipation needs, improves product adaptability and flexibility, and reduces energy consumption and environmental pollution.
Smart Images

Figure CN119685826A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal thermal conductive gasket preparation, and in particular to a high-quality preparation method of a metal thermal conductive gasket with enhanced process. Background Art
[0002] In modern industrial and high-tech fields, such as electronic equipment, high-power electrical equipment, aerospace, and new energy vehicles, efficient heat dissipation solutions are the core elements to ensure stable operation of equipment and extend its service life. Metal thermal pads, as an indispensable key component in the heat dissipation system, undertake the important task of transferring heat from the heat source to the heat dissipation device. Its thermal conductivity and thermal contact performance are directly related to the performance of the entire heat dissipation system and the reliability of the equipment.
[0003] Traditional methods for preparing metal thermal pads, such as machining, chemical etching or electroplating, can meet basic heat dissipation needs to a certain extent. However, with the development of science and technology and the improvement of industry standards, these methods have gradually exposed many shortcomings. First, it is difficult to accurately control the roughness of the surface of the metal thermal pad during the preparation process, resulting in limited thermal contact area and thermal conduction efficiency. Secondly, traditional preparation methods lack precision when processing specific thermal contact performance areas, making it difficult to meet the growing personalized heat dissipation needs. In addition, traditional methods also have problems such as high energy consumption and severe environmental pollution, which is not conducive to sustainable development.
[0004] As a high-precision processing technology, focused ion beam (FIB) has broad application prospects in the field of micro-nano manufacturing. However, traditional technology has several obvious shortcomings when using focused ion beam to process metal thermal pads. First, there is a lack of ion implantation pretreatment steps tailored to the material characteristics of metal thermal pads, which makes it difficult to accurately control the etching depth and shape during the etching process. Second, the traditional method fails to give full play to the advantages of focused ion beam in local fine processing and cannot achieve differentiated roughness customization in different areas. Third, the traditional technology lacks precise control of surface roughness and thermal contact performance during the processing, resulting in the performance and quality of the final product being difficult to meet the needs of high-end applications. Therefore, a new high-quality preparation method for metal thermal pads with enhanced process is urgently needed to improve the performance and quality of metal thermal pads. Summary of the invention
[0005] The purpose of the present invention is to make up for the shortcomings of the prior art and to provide a high-quality preparation method for a metal thermally conductive gasket with an enhanced process. The method can utilize focused ion beam technology to achieve high-precision processing of the surface of the metal thermally conductive gasket to improve its thermal contact performance and thermal conductivity efficiency. Through ion implantation pretreatment, the etching selectivity is enhanced, the etching depth and shape are better controlled, and high-precision milling and etching are performed using a focused ion beam. The surface roughness can be accurately controlled to meet specific thermal contact requirements. At the same time, the method can also perform fine processing in local areas that require specific thermal contact performance, thereby improving the stability and reliability of the thermal contact performance.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a high-quality metal thermal conductive gasket with enhanced process, the method comprising the following specific steps:
[0007] Raw material preparation: Provide a metal thermal pad substrate. The shape and size of the substrate are selected according to actual needs.
[0008] Ion implantation pretreatment: select ions that have good bonding with the metal gasket material and can enhance etching selectivity, and implant ions into the metal gasket to better control the depth and shape of etching during the processing;
[0009] Focused ion beam processing: Use a focused ion beam to perform high-precision milling and preliminary etching on the surface of the metal thermal pad. By controlling the parameters of the focused ion beam, areas of different roughness are formed on the metal surface. In the key area where the metal gasket contacts other components, its position and range are determined through heat dissipation system design analysis and heat flow simulation. During processing, the focused ion beam is used for precise processing to reduce the surface roughness. Spiral scanning is used for local fine scanning and high-resolution surface roughness measuring instruments are used to measure the surface roughness in real time. The ion beam parameters and scanning mode are fine-tuned according to the measurement results until the surface roughness of the key area meets the requirements. In the non-contact key area, adjustments are made according to specific functional requirements. Specific processing goals are determined through heat conduction analysis and heat dissipation demand assessment. The etching depth and scanning parameters are adjusted by controlling the focused ion beam etching time and beam density. The microstructure is observed using an electron microscope to evaluate whether the functional requirements are met. The etching parameters and scanning mode are further adjusted according to the results to optimize the processing effect;
[0010] Performance testing and quality inspection: The prepared metal thermal pads are subjected to performance testing and quality inspection. The performance and quality of the metal thermal pads are evaluated by adopting thermal conductivity testing, surface roughness measurement and microstructure observation methods.
[0011] Furthermore, in the raw material preparation step, the substrate material is selected from metals with good thermal conductivity including but not limited to copper, aluminum and silver, and the metal substrate is cleaned by washing with an organic solvent, rinsing with deionized water and drying.
[0012] Furthermore, in the ion implantation pretreatment step, ions are selected that have good bonding with the metal gasket material and can enhance etching selectivity, and the ions are selected from nitrogen ions, boron ions or carbon ions.
[0013] Furthermore, in the ion implantation pretreatment step, the metal gasket is subjected to ion implantation pretreatment, and the ion implantation parameters are ion energy of 10-100 keV and beam current density of 0.1-1 μA / cm 2 The injection time is 5-30 minutes.
[0014] Furthermore, in the focused ion beam processing step, the surface of the metal thermal conductive gasket is subjected to high-precision milling and preliminary etching using a focused ion beam, and the depth of the preliminary etching is 5-20 nanometers.
[0015] Furthermore, in the focused ion beam processing step, in the key area where the metal gasket contacts other parts, the focused ion beam is used for precise processing to reduce the surface roughness, the focused ion beam energy is reduced to 10-20keV, and the beam current density is adjusted to 0.1-0.3A / cm 2 , use spiral scanning for local fine scanning and use high-resolution surface roughness measuring instruments to measure the surface roughness in real time. The scanning speed is controlled at 1-3 mm / s. According to the measurement results, the ion beam parameters and scanning mode are fine-tuned until the surface roughness of the key area reaches 1-10 nanometers.
[0016] Furthermore, in the focused ion beam processing step, in the non-contact key area, adjustments are made according to specific functional requirements, and the specific processing goals are determined by thermal conduction analysis and heat dissipation demand assessment. The etching depth is adjusted by 100-200 nanometers, and the etching depth is adjusted by controlling the focused ion beam etching time and beam density. The scanning parameters are adjusted with a scanning angle of 45 degrees cross and a scanning spacing of 10-20 nanometers. The microstructure is observed using an electron microscope with a magnification of 1000-10000 times to evaluate whether the functional requirements are met. Based on the results, the etching parameters and scanning mode are further adjusted to optimize the processing effect.
[0017] Furthermore, in the performance test and quality inspection steps, a thermal conductivity testing device is used to measure the thermal conductivity of the metal thermally conductive gasket. The prepared gasket is placed in the testing device, a temperature gradient of 10-50 degrees Celsius is applied, and the heat flow and temperature difference through the gasket are measured to calculate the thermal conductivity. For surface roughness measurement: an atomic force microscope or a profilometer is used to measure the surface roughness of the metal thermally conductive gasket. For microstructure observation, a microscope is used to observe the microstructure of the metal thermally conductive gasket. The electron microscope has a magnification of 1000-10000 times to observe the directional arrangement of the thermally conductive filler and the bonding state with the metal surface, and the processing quality is evaluated. Based on the test and inspection results, the performance and quality of the metal thermally conductive gasket are evaluated.
[0018] Compared with the prior art, this method for preparing high-quality metal thermal conductive pads with enhanced process has the following beneficial effects:
[0019] 1. The present invention uses focused ion beam technology to perform high-precision processing on the surface of the metal thermally conductive gasket, which can accurately control the surface roughness, especially in the key areas in contact with other components, significantly reducing the surface roughness, thereby greatly increasing the thermal contact area and improving the heat conduction efficiency. This precise surface treatment not only optimizes the heat conduction path, but also reduces the resistance in the heat transfer process, so that the metal thermally conductive gasket can play a more efficient role in the heat dissipation system and significantly improve the overall heat dissipation performance.
[0020] 2. The present invention achieves nanometer-level control accuracy by precisely adjusting the parameters and scanning path of the focused ion beam, and can accurately customize the surface roughness of different local areas. This local fine processing capability enables the metal thermal conductive gasket to meet more complex and sophisticated heat dissipation requirements, thereby improving the adaptability and flexibility of the product.
[0021] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 It is a flow chart of a high-quality preparation method of a reinforced process metal thermal conductive pad;
[0024] Figure 2 The present invention is a flowchart of a focused ion beam processing method for high-quality preparation of a process-enhanced metal thermal conductive gasket. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Comparative Example 1
[0027] Copper was selected as the base material. Considering the heat dissipation requirements of specific electronic equipment, it was prepared into a rectangular shape with dimensions of 100 mm long, 50 mm wide and 2 mm thick. The metal base was cleaned. First, the metal gasket was immersed in an acetone solution, and the good solubility of acetone was used to remove impurities such as oil on the surface. The soaking time was 15 minutes. After that, it was rinsed with deionized water for multiple times, each rinse time was 2 minutes, to ensure that there were no residual impurities. Finally, it was placed in a well-ventilated and dust-free environment by natural air drying for 2 hours to ensure that the base surface was clean and dry.
[0028] After a series of material analysis and experimental tests, nitrogen ions were selected for implantation, and the ion implantation parameters were set to ion energy 50keV and beam density 0.5μA / cm 2 The injection time is 30 minutes. During the injection process, professional ion implantation equipment is used, and the stability and uniformity of the ion beam are monitored in real time. By adjusting the equipment parameters, it is ensured that the nitrogen ions can be evenly injected into the metal gasket to avoid local concentrations that are too high or too low.
[0029] Start the focused ion beam equipment. For the copper gasket, first perform preliminary etching on the entire surface. The ion beam energy is set to 20keV and the beam current density is 0.6A / cm 2 The scanning path selects linear scanning. During the etching process, the etching depth and surface flatness are observed in real time through a microscope. After multiple tests, it is determined that the etching depth is controlled at about 30 nanometers to ensure that the etching effect of the entire surface is uniform and consistent. The key area and non-key area are determined. The key area is the part in contact with the heat dissipation element. The key area is finely processed. The ion beam energy is reduced to 15keV, and the beam density is adjusted to 0.2A / cm 2, a spiral scanning mode is adopted with a scanning speed of 2 mm / s. During the processing, a high-resolution atomic force microscope is used to measure the surface roughness of the key areas in real time with a measurement accuracy of 0.8 nanometers. According to the measurement results, the ion beam parameters are continuously adjusted to ensure that the surface roughness of the key areas is controlled within 5 nanometers to improve the thermal contact area and heat conduction efficiency. For non-critical areas, the etching depth is adjusted to 150 nanometers according to the need to increase the surface area to improve the heat dissipation by thermal radiation. A cross scanning mode is adopted to create the microstructure with a scanning angle of 45 degrees and a scanning interval of 15 nanometers. An electron microscope is used to observe the microstructure of the non-critical areas with a magnification of 5000 times. By observing the changes in the microstructure, it is evaluated whether the etching effect meets the requirements of thermal radiation heat dissipation. If necessary, the etching parameters and scanning mode can be further adjusted to optimize the processing effect of non-critical areas.
[0030] Professional thermal conductivity test equipment is used to apply a temperature gradient of 40 degrees Celsius. The choice of this temperature gradient is based on the consideration of the operating temperature range of electronic equipment to ensure that the test results can accurately reflect the thermal conductivity performance of the metal thermal pad under actual working conditions. The heat flow and temperature difference through the pad are measured. High-precision heat flow sensors and temperature sensors are used to ensure the accuracy of the measurement results. The thermal conductivity is calculated based on the measurement results and compared with the design requirements to evaluate whether the thermal conductivity performance of the metal thermal pad meets expectations. In addition, a surface roughness measuring instrument is used to perform multi-point measurements on different areas of the metal thermal pad with a measurement accuracy of 0.5 nanometers. Multiple points are selected in key areas and non-key areas. measurement points, take the average value to ensure the reliability of the measurement results, evaluate the surface roughness distribution, and judge whether it meets the design requirements. If the surface roughness is uneven or exceeds the specified range, the processing parameters of the focused ion beam can be adjusted or rework can be performed. In addition, microscopes and other equipment are used. The electron microscope has a magnification of 8000 times to observe the directional arrangement of the thermal conductive filler and the bonding state with the metal surface. For metal gaskets containing thermal conductive fillers, focus on evaluating the distribution and orientation of the fillers in different areas, as well as the bonding strength with the metal substrate. If it is found that the filler is unevenly distributed or the bonding is not tight, the processing technology can be adjusted or appropriate additives can be added to improve the performance and quality of the metal thermal conductive gasket.
[0031] In this comparative example, in terms of heat conduction, the thermal contact area and heat conduction efficiency between the key area and the heat dissipation element are good, which can meet the heat dissipation requirements of general electronic equipment. The thermal radiation heat dissipation capacity of the non-key area is moderate, and the overall heat dissipation performance is relatively balanced.
[0032] Comparative Example 2
[0033] Copper was selected as the base material and prepared into a rectangular shape with dimensions of 100 mm long, 50 mm wide and 2 mm thick. The metal base was cleaned. First, acetone was used as an organic solvent to remove impurities such as surface oil, and then it was rinsed multiple times with deionized water. Finally, it was naturally air-dried to ensure that the base surface was clean and dry.
[0034] After experimental testing, nitrogen ions were selected for implantation, and the ion implantation parameters were set to ion energy 50keV and beam density 0.5μA / cm 2 , the injection time is 30 minutes.
[0035] Start the focused ion beam equipment. For the copper gasket, first perform preliminary etching on the entire surface. The ion beam energy is set to 18keV and the beam current density is 0.55A / cm 2 The scanning path selects linear scanning, the etching depth is controlled at about 25 nanometers, and the key area and non-key area are determined. The key area is the part in contact with the heat dissipation element. The key area is finely processed, the ion beam energy is reduced to 14keV, and the beam density is adjusted to 0.18A / cm 2 , a spiral scanning mode was adopted with a scanning speed of 1.8 mm / s. A high-resolution atomic force microscope was used to measure the surface roughness of the critical areas in real time with a measurement accuracy of 0.7 nanometers. The surface roughness of the critical areas was controlled within 4.5 nanometers. For non-critical areas, the etching depth was adjusted to 140 nanometers according to the need to increase the surface area to improve thermal radiation and heat dissipation. A cross scanning mode was adopted to create the microstructure. The scanning angle was 40 degrees cross and the scanning spacing was 14 nanometers. An electron microscope was used to observe the microstructure of the non-critical areas with a magnification of 4500 times.
[0036] Professional thermal conductivity testing equipment is used to apply a temperature gradient of 40 degrees Celsius, measure the heat flow and temperature difference through the gasket, calculate the thermal conductivity, and use a surface roughness measuring instrument to perform multi-point measurements on different areas of the metal thermal conductive gasket with a measurement accuracy of 0.5 nanometers to evaluate the surface roughness distribution. In addition, microscopes and other equipment are used, with an electron microscope with a magnification of 8000 times, to evaluate the directional arrangement of the thermal conductive filler and its bonding state with the metal surface.
[0037] In this comparative example, the surface roughness of the key area is smaller, the thermal contact with the heat dissipation element is closer, the heat conduction efficiency is further improved, the etching depth and scanning parameter adjustment of the non-critical area make the increase in surface area relatively small, and the thermal radiation heat dissipation capacity is slightly weaker than that of comparative example 1, but the overall performance is relatively refined, which is suitable for scenarios with high requirements for thermal conduction and relatively mild heat dissipation environment.
[0038] Comparative Example 3
[0039] Copper was selected as the base material and prepared into a rectangular shape with dimensions of 100 mm long, 50 mm wide and 2 mm thick. The metal base was cleaned. First, acetone was used as an organic solvent to remove impurities such as surface oil, and then it was rinsed multiple times with deionized water. Finally, it was naturally air-dried to ensure that the base surface was clean and dry.
[0040] After experimental testing, nitrogen ions were selected for implantation, and the ion implantation parameters were set to ion energy 50keV and beam density 0.5μA / cm 2 , the injection time is 30 minutes.
[0041] Start the focused ion beam equipment. For the copper gasket, first perform preliminary etching on the entire surface. The ion beam energy is set to 22keV and the beam current density is 0.65A / cm 2 The scanning path selects linear scanning, the etching depth is controlled at about 35 nanometers, and the key area and non-key area are determined. The key area is the part in contact with the heat dissipation element. The key area is finely processed, the ion beam energy is reduced to 16keV, and the beam density is adjusted to 0.22A / cm 2 , a spiral scanning mode is adopted with a scanning speed of 2.2 mm / s. A high-resolution atomic force microscope is used to measure the surface roughness of the critical area in real time with a measurement accuracy of 0.9 nanometers. The surface roughness of the critical area is controlled within 6 nanometers. For non-critical areas, the etching depth is adjusted to 160 nanometers according to the need to increase the surface area to improve thermal radiation and heat dissipation. A cross scanning mode is adopted to create the microstructure. The scanning angle is 50 degrees cross and the scanning spacing is 16 nanometers. An electron microscope is used to observe the microstructure of the non-critical area with a magnification of 5500 times.
[0042] Professional thermal conductivity testing equipment is used to apply a temperature gradient of 40 degrees Celsius, measure the heat flow and temperature difference through the gasket, calculate the thermal conductivity, and use a surface roughness measuring instrument to perform multi-point measurements on different areas of the metal thermal conductive gasket with a measurement accuracy of 0.5 nanometers to evaluate the surface roughness distribution. In addition, microscopes and other equipment are used, with an electron microscope with a magnification of 8000 times, to evaluate the directional arrangement of the thermal conductive filler and its bonding state with the metal surface.
[0043] In this comparative example, the ion beam parameters in the key area are relatively high, the surface roughness is slightly larger, and the thermal conduction efficiency is slightly different from that of comparative example 1, but it can still meet higher heat dissipation requirements. The etching depth and scanning parameters in the non-critical area are larger, the surface area is increased more, and the thermal radiation heat dissipation capacity is relatively strong, which is suitable for use in situations where the heat dissipation requirements are high and the heat dissipation environment is more complex.
[0044] Comparative Example 4
[0045] Copper was selected as the base material and prepared into a rectangular shape with dimensions of 100 mm long, 50 mm wide and 2 mm thick. The metal base was cleaned. First, acetone was used as an organic solvent to remove impurities such as surface oil, and then it was rinsed multiple times with deionized water. Finally, it was naturally air-dried to ensure that the base surface was clean and dry.
[0046] After experimental testing, nitrogen ions were selected for implantation, and the ion implantation parameters were set to ion energy 50keV and beam density 0.5μA / cm 2 , the injection time is 30 minutes.
[0047] Start the focused ion beam equipment. For the copper gasket, first perform preliminary etching on the entire surface. The ion beam energy is set to 21keV and the beam current density is 0.62A / cm 2 The scanning path selects linear scanning, the etching depth is controlled at about 32 nanometers, and the key area and non-key area are determined. The key area is the part in contact with the heat dissipation element. The key area is finely processed, the ion beam energy is reduced to 15.5keV, and the beam density is adjusted to 0.21A / cm 2 , a spiral scanning mode was adopted with a scanning speed of 2.1 mm / s. A high-resolution atomic force microscope was used to measure the surface roughness of the critical areas in real time with a measurement accuracy of 0.85 nanometers. The surface roughness of the critical areas was controlled within 5.5 nanometers. For non-critical areas, the etching depth was adjusted to 155 nanometers according to the need to increase the surface area to improve thermal radiation and heat dissipation. A cross scanning mode was adopted to create the microstructure. The scanning angle was 48 degrees cross and the scanning spacing was 15.5 nanometers. An electron microscope was used to observe the microstructure of the non-critical areas with a magnification of 5200 times.
[0048] Professional thermal conductivity testing equipment is used to apply a temperature gradient of 40 degrees Celsius, measure the heat flow and temperature difference through the gasket, calculate the thermal conductivity, and use a surface roughness measuring instrument to perform multi-point measurements on different areas of the metal thermal conductive gasket with a measurement accuracy of 0.5 nanometers to evaluate the surface roughness distribution. In addition, microscopes and other equipment are used, with an electron microscope with a magnification of 8000 times, to evaluate the directional arrangement of the thermal conductive filler and its bonding state with the metal surface.
[0049] In this comparison, the overall parameters are between comparison examples 1 and 3, the performance is relatively balanced, the thermal conduction efficiency in key areas and the thermal radiation heat dissipation capacity in non-key areas are also at a medium level, which is suitable for scenarios with moderate heat dissipation requirements.
[0050] In summary, the high-quality preparation method of the enhanced process metal thermally conductive gasket of the present invention provides a specific base material and cleans it, performs ion implantation pretreatment on the metal gasket, uses a focused ion beam to perform high-precision milling, etching and roughness adjustment on the surface of the metal thermally conductive gasket, divides the critical area and non-critical area for separate processing, and passes strict performance testing and quality inspection. It is possible to prepare a metal thermally conductive gasket with good thermal conductivity and a specific surface roughness distribution. According to the above four comparative examples, by adjusting the parameters of the focused ion beam, the performance of the critical area and non-critical area of the metal gasket can be targetedly optimized while other conditions remain unchanged, thereby improving the heat dissipation effect and quality of the metal thermally conductive gasket as a whole.
[0051] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and range of equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high-quality preparation method for a metal thermally conductive gasket with enhanced process, characterized in that: The method comprises the following specific steps: Raw material preparation: Provide a metal thermal pad substrate. The shape and size of the substrate are selected according to actual needs. Ion implantation pretreatment: select ions that have good bonding with the metal gasket material and can enhance etching selectivity, and implant ions into the metal gasket to better control the depth and shape of etching during the processing; Focused ion beam processing: Use a focused ion beam to perform high-precision milling and preliminary etching on the surface of the metal thermal pad. By controlling the parameters of the focused ion beam, areas of different roughness are formed on the metal surface. In the key area where the metal gasket contacts other components, its position and range are determined through heat dissipation system design analysis and heat flow simulation. During processing, the focused ion beam is used for precise processing to reduce the surface roughness. Spiral scanning is used for local fine scanning and high-resolution surface roughness measuring instruments are used to measure the surface roughness in real time. The ion beam parameters and scanning mode are fine-tuned according to the measurement results until the surface roughness of the key area meets the requirements. In the non-contact key area, adjustments are made according to specific functional requirements. Specific processing goals are determined through heat conduction analysis and heat dissipation demand assessment. The etching depth and scanning parameters are adjusted by controlling the focused ion beam etching time and beam density. The microstructure is observed using an electron microscope to evaluate whether the functional requirements are met. The etching parameters and scanning mode are further adjusted according to the results to optimize the processing effect; Performance testing and quality inspection: The prepared metal thermal pads are subjected to performance testing and quality inspection. The performance and quality of the metal thermal pads are evaluated by adopting thermal conductivity testing, surface roughness measurement and microstructure observation methods.
2. The method for preparing a high-quality metal thermally conductive gasket with enhanced process according to claim 1, characterized in that: In the raw material preparation step, the substrate material is selected from metals with good thermal conductivity including but not limited to copper, aluminum and silver, and the metal substrate is cleaned by washing with an organic solvent, rinsing with deionized water and drying.
3. The method for preparing a high-quality metal thermally conductive gasket with enhanced process according to claim 1, characterized in that: In the ion implantation pretreatment step, ions are selected that have good bonding with the metal gasket material and can enhance etching selectivity, and the ions are selected from nitrogen ions, boron ions or carbon ions.
4. The method for preparing a high-quality metal thermally conductive gasket with enhanced process according to claim 1, characterized in that: In the ion implantation pretreatment step, the metal gasket is subjected to ion implantation pretreatment, and the ion implantation parameters are ion energy of 10-100 keV and beam current density of 0.1-1 μA / cm 2 The injection time is 5-30 minutes.
5. The method for preparing a high-quality metal thermally conductive gasket with enhanced process according to claim 1, characterized in that: In the focused ion beam processing step, the surface of the metal thermal conductive pad is subjected to high-precision milling and preliminary etching using a focused ion beam, and the depth of the preliminary etching is 5-20 nanometers.
6. The method for preparing a high-quality metal thermally conductive gasket with enhanced process according to claim 1, characterized in that: In the focused ion beam processing step, in the key area where the metal gasket contacts other parts, the focused ion beam is used to accurately process and reduce the surface roughness, and the focused ion beam energy is reduced to 10-20keV, and the beam current density is adjusted to 0.1-0.3A / cm 2 , use spiral scanning for local fine scanning and use high-resolution surface roughness measuring instruments to measure the surface roughness in real time. The scanning speed is controlled at 1-3 mm / s. According to the measurement results, the ion beam parameters and scanning mode are fine-tuned until the surface roughness of the key area reaches 1-10 nanometers.
7. The method for preparing a high-quality metal thermally conductive gasket with enhanced process according to claim 1, characterized in that: In the focused ion beam processing step, in the non-contact key area, adjustments are made according to specific functional requirements, and the specific processing goals are determined by thermal conduction analysis and heat dissipation demand assessment. The etching depth is adjusted by 100-200 nanometers, and the etching depth is adjusted by controlling the focused ion beam etching time and beam density. The scanning parameters are adjusted, the scanning angle is 45 degrees cross, the scanning spacing is 10-20 nanometers, and the microstructure is observed using an electron microscope with a magnification of 1000-10000 times to evaluate whether the functional requirements are met. According to the results, the etching parameters and scanning mode are further adjusted to optimize the processing effect.
8. The method for preparing a high-quality metal thermally conductive gasket with enhanced process according to claim 1, characterized in that: In the performance test and quality inspection steps, a thermal conductivity testing device is used to measure the thermal conductivity of the metal thermally conductive gasket. The prepared gasket is placed in the testing device, a temperature gradient of 10-50 degrees Celsius is applied, and the heat flow and temperature difference through the gasket are measured to calculate the thermal conductivity. For surface roughness measurement: an atomic force microscope or a profilometer is used to measure the surface roughness of the metal thermally conductive gasket. For microstructure observation, a microscope is used to observe the microstructure of the metal thermally conductive gasket. The electron microscope has a magnification of 1000-10000 times to observe the directional arrangement of the thermally conductive filler and the bonding state with the metal surface, and the processing quality is evaluated. According to the test and inspection results, the performance and quality of the metal thermally conductive gasket are evaluated.
Citation Information
Patent Citations
Method for processing fine curved surface of glass surface layer part
JP2013256395A
Method of durability assessment for thin protective coatings on materials under high energy effects
RU2530784C1
Copper clad laminate and metalization method for micropores thereof
WO2019140630A1